Mutation-Driven Immune Microenvironments in Non-Small Cell Lung Cancer: Unrevealing Patterns through Cluster Analysis - Kim, Youngtaek; Hwang, Joon Yeon; Kim, Dong Kwon; Lee, Seul; Kang, Seong-san; Baek, Sujeong; Yang, Seung Min; Kim, Mi Hyun; Han, Heekyung; Jeong, Seong Su; Lee, Chai Young; Han, Yu Jin; et al. (Yonsei medical journal, 2024)
We aimed to comprehensively analyze the immune cell and stromal components of tumor microenvironment at the single-cell level and identify tumor heterogeneity among the major top-derived oncogene mutations in non-small cell lung cancer (NSCLC) using single-cell RNA sequencing (scRNA-seq) data. The scRNA-seq dataset utilized in this study comprised 64369 primary tumor tissue cells from 21 NSCLC patients, focusing on mutations in , , , , , and the wild-type. Tumor immune microenvironment (TIM) analysis revealed differential immune responses across NSCLC mutation subtypes. TIM analysis revealed different immune responses across the mutation subtypes. Two mutation clusters emerged: , , and + mutations (MC1); and , , and mutations (MC2). MC1 showed higher tertiary lymphoid structures signature scores and enriched populations of C2-T-IL7R, C3-T/NK-CXCL4, C9-T/NK-NKG, and C1-B-MS4A1 clusters than cluster 2. Conversely, MC2 cells exhibited higher expression levels of , , and chemokines linked to alternative immune pathways. Remarkably, co-occurring and mutations were grouped as MC1. + mutations showed upregulation of peptide synthesis and higher synthetic processes, as well as differences in myeloid and T/NK cells compared to mutations. In T/NK cells, + mutations showed a higher expression of features related to cell activity and differentiation, whereas mutations showed the opposite. Our research indicates a close association between mutation types and tumor microenvironment in NSCLC, offering insights into personalized approaches for cancer diagnosis and treatment.